Under erasure - Loftiss, Luke (My University, 2014)
This thesis is a collection of eleven short, unrelated stories. These stories range in length from thirty-three to two pages. They are organized according to how I sensed they should be when I drew up the table of contents. I had not planned on there being any unifying theme to this collection but because I wrote most of these stories during the same short span of weeks, they couldn't keep from being influenced by what happened to be on my mind at the time. I didn't realize there was anything on my mind but when I read the stories I found that they were mostly asking two questions: What is beauty and how do we experience it? What is a mind and how do we experience it? Four questions. Whatever. Writers whose ideas influenced this collection include: Felisberto Hernandez, Franz Kafka, Jose Saramago, Philip K. Dick and Douglas Hofstadter. The title is meant to suggest that the collection is necessary if not sufficient..
Keywords: Short stories; Fiction